Interviewers' approaches to questioning vulnerable child witnesses: The influences of developmental level versus intellectual disability status. (11th March 2017) - Brown, Deirdre; Lewis, Charlie; Stephens, Emma; Lamb, Michael
Abstract : Purpose: Children with intellectual disabilities (CWIDs) are vulnerable to victimization, but we know little about how to interview them about possible maltreatment. We examined whether interviewers used proportionally more direct and option‐posing, and fewer open questions, with CWID than with typically developing (TD) children or with less mature children regardless of disability, taking into account the contribution of the amount of information conveyed by the child. Method: One hundred and twelve children (4–12 years) participated in a staged event and were interviewed 1 week later using the NICHD Investigative Interview Protocol. We examined the proportions of different interview prompts posed to CWID of either mild (CWID‐Mild) or moderate (CWID‐Moderate) severity compared with typically developing children matched for chronological (CA) and mental (MA) age. Results: Even when controlling for the amount that the child said, the overall number and relative proportions of each question type posed to each group varied. Interviewers asked more cued invitations and fewer direct questions of CA‐matched children than younger TD participants or both CWID groups. Option‐posing questions comprised a larger proportion of the interviews with both ID groups than with CA matches. The few suggestive questions were posed more to CWID‐Moderate. Conclusions: Although research has shown that CWID and young TD children can provide reliable information in response to very open prompting, interviewers tend not to ask such questions. Interviewing strategy was influenced by both developmental level and intellectual disability status, in conjunction with children's individual contributions to the interview, emphasizing the importance of interviewers' understanding the capacities and vulnerabilities of the children they interview from both a developmental and cognitive perspective.